A tribute to Fernando A. Silveira and his contributions to bee research - Almeida, Eduardo A. B. (Zootaxa, 2024)
Fernando A. Silveira had the unique combination of being a sagacious scientist and a remarkable human being. Throughout his career, he made significant contributions to understanding bee diversity and keenly spread this scientific information to the academic community at large and beyond the university walls. His rich character, warm heart, strong voice and laughter are missed by those privileged to be Fernando’s students, friends, mentors, and family. In this volume, we honor Fernando A. Silveira, who prematurely passed away at the age of 62, leaving three sons, his wife, and numerous friends.